The effects of JM-20 on the glutamatergic system in synaptic vesicles, synaptosomes and neural cells cultured from rat brain. (February 2015) - Nuñez-Figueredo, Yanier; Pardo Andreu, Gilberto L.; Oliveira Loureiro, Samanta; Ganzella, Marcelo; Ramírez-Sánchez, Jeney; Ochoa-Rodríguez, Estael; Verdecia-Reyes, Yamila; Delgado-Hernández, René; Souza, Diogo O.
Highlights: JM-20 is a novel neuroprotective agent. JM-20 reduced the glutamate concentration in cerebrospinal fluid from ischemic rats. JM-20 impairs H-ATPase activity and consequently reduces vesicular glutamate uptake. JM-20 also inhibits glutamate release from brain synaptosomes. JM-20 increases glutamate uptake in astrocytes and co-cultured neurons/astrocytes. Abstract: JM-20 (3-ethoxycarbonyl-2-methyl-4-(2-nitrophenyl)-4, 11-dihydro-1H-pyrido[2, 3-b][1, 5]benzodiazepine) is a novel benzodiazepine dihydropyridine hybrid molecule, which has been shown to be a neuroprotective agent in brain disorders involving glutamate receptors. However, the effect of JM-20 on the functionality of the glutamatergic system has not been investigated. In this study, by using different in vitro preparations, we investigated the effects of JM-20 on ( i ) rat brain synaptic vesicles (L-[ 3 H]-glutamate uptake, proton gradient built-up and bafilomycin-sensitive H + -ATPase activity), ( ii ) rat brain synaptosomes (glutamate release) and ( iii ) primary cultures of rat cortical neurons, astrocytes and astrocyte–neuron co-cultures (L-[ 3 H]-glutamate uptake and glutamate release). We observed here that JM-20 impairs H + -ATPase activity and consequently reduces vesicular glutamate uptake. This molecule also inhibits glutamate release from brain synaptosomes and markedly increases glutamate uptake in astrocytes alone, and co-cultured neurons and astrocytes. The impairment of vesicular glutamate uptake by inhibition of the H + -ATPase caused by JM-20 could decrease the amount of the transmitter stored in synaptic vesicles, increase the cytosolic levels of glutamate, and will thus down-regulate neurotransmitter release. Together, these results contribute to explain the anti-excitotoxic effect of JM-20 and its strong neuroprotective effect observed in different in vitro and in vivo models of brain ischemia.